ENHANCING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXTS USING THE STRATEGY OF STORY MAPPING - Rijalul Fawaid; Wijayadi; Nur Fitriah (PROCEEDING UMSURABAYA, 2026)
This study aims to improve students’ reading comprehension of narrative texts through the implementation of the Story Mapping Strategy. The research subjects were 35 students of class X-09 at SMAN 17 Surabaya. The method used was Classroom Action Research (CAR) following the model of Kemmis & McTaggart (1988), which consists of planning, implementation, observation, and reflection in two cycles. Data was collected through reading comprehension tests (pre-test and post-test), observations, and interviews. The result of research showed a significant improvement in students' reading comprehension after applying the Story Mapping Strategy. The students' average score increased from 61,5 in the pre-test to 83,1 in the post-test of the second cycle. Additionally, the percentage of students achieving the Minimum Competency Criteria (KKM) increased from 24 % to 85,7 %. The Story Mapping that implemented helped students effectively organize information from narrative texts, thereby enhancing their comprehension. This strategy allowed students to identify key elements of the story, such as characters, setting, and plot, which contributed to their understanding of the narrative text. Based on findings, Story Mapping has been proven to be an effective strategy in teaching reading comprehension of narrative texts at the high school level. Therefore, this strategy is recommended for teachers to enhance students’ reading comprehension skills.